EFEKTIVITAS UPAYA PENANGANAN KEKERASAN BERBASIS GENDER DI YUNANI: Analisis Istanbul Convention 2018-2022 - Adelia Citra Dwi Trisnawati; Firsty Chintya Laksmi Perbawani (Halu Oleo University, 2024)
Gender-based violence is a phenomenon that is widespread throughout the world and is a concern for human security. For this reason, the Council of Europe formed the Istanbul Convention to combat gender-based violence, especially in Europe. The main focus of this research is to analyze the effectiveness of the Istanbul Convention as an international regime in Greece, the country with the lowest level of gender equality in Europe, using the Regime Effectiveness theory. The research method uses an explanatory research type which aims to explain the position of the variables studied and the cause-and-effect relationships that exist between the variables. The results of this research prove that the Istanbul Convention can be categorized as an effective international regime in Greece, along with the implementation of policies that are in line with the values and objectives of the convention. Thus, this research shows that the Istanbul Convention was able to achieve its effectiveness as an international regime in Greece.